Omission of axillary lymph node dissection in clinically node-negative breast cancer with sentinel node metastasis: a systematic review and metaanalysis of noninferiority randomized clinical trials - Miranda, Maria Clara Ramos; Santos, Charles Karel Martins; Silva, Antonio Márcio Teodoro Cordeiro (Mastology, 2026)
Objective: To evaluate the de-escalation of axillary lymph node dissection (ALND) in clinically node-negative (cN0) breast cancer with sentinel node (SN) metastasis. Methods: A systematic review and meta-analysis (CRD420251000419) was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines and the PICOTS (patient/population, intervention, comparison, outcome, timing, and setting) framework. The databases PubMed, Embase, and Cochrane were searched for randomized clinical trials with ≥5-year follow-up that evaluated ALND omission in cN0 breast cancer with positive SN, assessing overall survival, disease-free survival, locoregional recurrence, or complications. Pooled hazard ratios (HR) and risk ratios (RR) were calculated using R software, with 95% confidence intervals (CI). Substantial heterogeneity was defined as I²>25%. A margin of 1.25 was set to assess non-inferiority (pni). Results: Eight randomized clinical trials were included, comprising 7,798 patients (no ALND: 50.6%; ALND: 49.4%). Omitting ALND was non-inferior for overall survival (HR 0.96; 95%CI 0.75–1.23; I²=12.9%; p=0.731; pni=0.0174) and disease-free survival (HR 1.02; 95%CI 0.89–1.16; I²=21.6%; p=0.791; pni=0.0013), but inferior for locoregional recurrence (HR 1.00; 95%CI 0.76–1.32; I²=20.6%; p=0.999; pni=0.0578). Sensitivity analysis showed similar results for 10-year endpoints. Omitting ALND significantly reduced the risk of lymphedema (RR 0.33; 95%CI 0.19–0.59; I²=35.9%; p=0.009). Subgroup analysis showed no significant disease-free survival differences by estrogen receptor status (positive vs. negative; p=0.1656), number of metastatic SNs (1 vs. ≥2; p=0.4632), tumor size (<2 vs. ≥2 cm; p=0.8169), and age (<65 vs. ≥65 years; p=0.9971). Conclusion: Omitting ALND provides equivalent overall survival and disease-free survival while reducing lymphedema, although non-inferiority in locoregional recurrence was not demonstrated